Devolution and human resources in primary healthcare in rural Mali - Dao Dramane; Lodenstein Elsbet (BMC, 2011)
Abstract Devolution, as other types of decentralization (e.g. deconcentration, delegation, privatization), profoundly changes governance relations in the health system. Devolution is meant to affect performance of the health system by transferring responsibilities and authority to locally elected governments. The key question of this article is: what does devolution mean for human resources for health in Mali? This article assesses the key advantages and dilemmas associated with devolution such as responsiveness to local needs, downward accountability and health worker retention. Challenges of politics and capacities are also addressed in relation to human resources for health at the local level. Examples are derived from experiences in Mali with a capacity development programme and from case studies of other countries. It is not research findings that are presented, but highlights of key issues at stake aimed at inspiring the debate in Mali and elsewhere. A first lesson from the discussion suggests that in the context of human resources for health, decentralization of authority and resources is not the main issue. The challenge is to develop or strengthen accountability of those who decide and act, whether they are local politicians, bureaucrats or community representatives. If decentralization policies do not address public accountability, they will not fundamentally change human resource management, quality and equity of staffing. A second lesson is that successful devolution requires innovations in capacity development of all actors involved and in designing effective incentive measures. A final key conclusion is that the topic of devolution policy and its effects on human resources for health, and vice versa, merit more attention. A better understanding may lead to more appropriate policy designs and better preparation for the actors involved in countries that are embarking on decentralization, as is the case in Mali.